EXPORT SALES, FIRM AGE, AND REVENUE GROWTH : THEIR IMPACT ON FINANCIAL PERFORMANCE WITH DEBT MATURITY AS A MODERATOR IN INDONESIAN MANUFACTURING FIRMS - Aris, Moh; Setiadi , Pompong Budi; Rahayu, Sri (Tekmapro, 2025)
This research investigates the impact of export sales, firm age, and revenue growth on the financial performance of manufacturing companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023, while examining the moderating role of debt maturity. The research highlights the significance of growth strategies and debt structure management in enhancing firm performance amid global competition. A quantitative approach is employed using multiple linear regression and Moderated Regression Analysis (MRA) on a sample of 30 purposively selected companies over five years. The results show that export sales do not significantly influence financial performance, whereas firm age and revenue growth have a significant positive effect. Collectively, the independent variables significantly influence financial performance. Debt maturity moderates the relationship by strengthening the effect of revenue growth and weakening the effect of firm age, while it does not moderate the impact of export sales. These findings offer theoretical contributions to financial management literature and practical insights for corporate decision-makers in managing long-term debt and designing effective growth strategies. The research also lays the groundwork for future research involving external macroeconomic variables as potential moderators. Keywords : Export Sales, Firm Age, Revenue Growth, Financial Performance, ROA, Debt Maturity, ..Moderated Regression